A nonparametric examination of capital-skill complementarity - Daniel J. Henderson (Institute for the Study of Labor (IZA), 2008)
This paper uses nonparametric kernel methods to construct observation-specific elasticities of substitution for a balanced panel of 73 developed and developing countries to examine the capital-skill complementarity hypothesis. The exercise shows some support for capital-skill complementarity, but the strength of the evidence depends upon the definition of skilled labor and the elasticity of substitution measure being used. The added flexibility of the nonparametric procedure is also able to uncover that the elasticities of substitution vary across countries, groups of countries and time periods.
urn:nbn:de:101:1-20081216190
Keywords: C14; 330; Capital-skill complementarity; elasticity of substitution; nonparametric kernel; stochastic dominance; Faktorsubstitution; Kapital; Qualifikation; Nichtparametrisches Verfahren; Schätzung; Welt